2018
DOI: 10.3389/fchem.2018.00217
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Photoresponsive Macromolecule for Biomedical Application

Abstract: Azobenzene, a photo switcher, has attracted increasing interest due to its structural response to photo stimulus in the field of information science and chemical sensing in the recent decades. However, limited water solubility and cytotoxicity restrained their applications in the biomedical field. In research, HA-AZO has been designed as a water soluble photo switcher in biomedical application. Synthesized HA-AZO had good water-solubility and a stable π-π* transition absorbance peak trans-isomer. With exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Numerous attempts have been made to increase the thermostability of the cis form, including the immobilization of AZO onto material surfaces, graing of AZO to a macromolecule, copolymerization, and cyclization. 2,4,6,8,9 Similar to these studies, we designed a polysaccharide derivative and AZO copolymers as photoswitches, and found that the thermostability of the cis form could be improved and controlled by environmental parameters as well as structural parameters such as temperature, light density, solvent, and chain characteristics. 9 Although these progresses have realized the application of AZOs as photo-switches, ultraviolet band excitation source has some disadvantages in extending the applications of smart molecules.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Numerous attempts have been made to increase the thermostability of the cis form, including the immobilization of AZO onto material surfaces, graing of AZO to a macromolecule, copolymerization, and cyclization. 2,4,6,8,9 Similar to these studies, we designed a polysaccharide derivative and AZO copolymers as photoswitches, and found that the thermostability of the cis form could be improved and controlled by environmental parameters as well as structural parameters such as temperature, light density, solvent, and chain characteristics. 9 Although these progresses have realized the application of AZOs as photo-switches, ultraviolet band excitation source has some disadvantages in extending the applications of smart molecules.…”
Section: Introductionmentioning
confidence: 86%
“…7 Moreover, the photobleaching phenomenon was also found in the small AZO molecule derivatives. 8 These drawbacks restrict their application as photo-switches. Numerous attempts have been made to increase the thermostability of the cis form, including the immobilization of AZO onto material surfaces, graing of AZO to a macromolecule, copolymerization, and cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…9 Light is a very attractive stimulus as it provides an additional spatio-temporal control over the selfassembly process, 3 however, examples of light-triggered supramolecular materials are mostly limited to the photo-switchable azobenzene moiety, alone or in cyclodextrin inclusion complexes, 10 and are known to lack stability due to the retro-isomerisation of azobenzene under physiological conditions. 11 Examples of photo-initiated self-assembled polysaccharide hydrogels and materials are rare, with few examples using azobenzene-functionalised hyaluronic acid, 12 cellulose, 13 xylan 14 or dextran. 15 The development of polysaccharide-based materials has been a very active area of research over the last few years, mainly owing to their low-cost, abundancy, non-toxicity, and natural bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, as a kind of stimuli-response material, photo switches have become new favorites in fields that require switching effects, including information science and chemical sensing due to structural changes in light. As a member of the photo switches, azobenzene (AZO) possesses two different reversible isomers (trans and cis) (Beharry and Woolley, 2011 ; Bian et al, 2016 ; Michael Kathan, 2017 ; Chen et al, 2018 ; Lerch et al, 2018 ; Pang et al, 2018 , 2019 ). The reversible isomerization could be realized upon light excitation and thermal transition.…”
Section: Introductionmentioning
confidence: 99%
“…The reversible isomerization could be realized upon light excitation and thermal transition. But the thermal transition is influenced by either the external environment or internal structure of the AZO family, which bring problems of photobleaching, instability, and uncontrollability (Pang et al, 2018 , 2019 ). In order to overcome problems, measures of substitute modifying, grafting, copolymerization, and immobilization have been used to improve the stability and controllability including our previous studies (Deka et al, 2015 ; Liu et al, 2015 ; Lin et al, 2016 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%